The ‘Then’ and ‘Now’ Environmental and Security Obstacles and Prospects of Maritime Industry in Nigeria - Big-Alabo, Sotonye; Ezugwu, Umezurike J (Titian: Jurnal Ilmu Humaniora, 2023)
The movement of goods and services along inland waterways is one of the oldest means of transporting goods and services from one point to another. However, the inland waterways in Nigeria, including navigable rivers, lakes, creeks, lagoons, and canals, face numerous problems and obstacles, such as sea piracy, terrorism, smuggling, kidnapping, and pollution. These and a host of other issues have truncated the achievements and development of the Nigerian maritime industry. However, to deal with the highlighted issues and excel in the maritime industry, there is a need to guard against environmental pollution through the application of environmental ethics and secure the inland waterways using maritime security operatives and agencies. Hence, inland water transportation offers the most economical, energy-efficient, and environmentally sustainable means of transporting all types of cargo from place to place. In view of this, Africa in general and Nigeria in particular should reflect on the development and management of this sea-borne trade, which is critical and cardinal to the development of international trade with other nations of the world. Since maritime transport is the propelling anchor and evolving force that brings about substantive revenue and helps in the survival of both national economic growth and the exportation of hydrocarbons, we used the hermeneutical method of philosophy to drive home the points of this research.